Craniofacial morphology of Class lll malocclusion in relation with genetic mutation - Nowrin, Shifat A; Basri, Rehana; Alam, Mohammad Khursheed; Jaafar, Saidi; Mokhtar@Makhtar, Khairani Idah (2016)
Objective: The purpose of this study was to compare the relation of craniofacial structures of mutation and non mutation group in class III malocclusion of Malaysian Malay families and their three generations. methodology: Three generations of Malaysian Malay families with an average age 22.50 (+/-5.30), 53.50 (+/-10.06) and 79.20 (+/-9.35) years of each generation respectively were elected for this study. Cephalometric radiographs of these families were taken for further analysis. All landmarks were positioned, determined and consequently tracings were completed using Romexis software (Planmeca, Finland) to accomplish craniofacial morphology investigation. The statistical comparisons of the mutation and non-mutation group were directed with t test and analysis of variance (ANOVA) was applied to evaluate the values for three generations in class III malocclusion among all measurements. Results: Current study revealed that in mutation group, there are significant differences in Co-Gn-B and SN-MP variables compare to non-mutation group. However, almost all craniofacial variables show no significant differences among three generations. Conclusions: This study may suggest that in mutation group mandible is more deviated from cranial base and there are almost no skeletal changes among three generations in case of class III malocclusion.